Dialogues between Freire’s concept of ideology and decoloniality (Revista Contexto & Educação, 2024)
Ideology is one of the fundamental concepts in Paulo Freire's work, and is also one of the most important in Marxist thought. A concept that not only helps us to better understand our reality and its contradictions, but also serves as an invitation to political struggle, revealing to us why to fight, what to fight for and what to fight against. In this sense, the concept of ideology converges unequivocally with colonial thought, which, just as Freire did, strives to reveal the disguises of power and the way in which it works to shape our feeling, thinking and acting in order to maintain the status quo and consequently its privilege. This article will seek to delve deeper into the existing approximations between Paulo Freire's proposal and decolonial thought, in the fight against the ideology developed by these theoretical perspectives and how both can contribute to the social transformations that are necessary when they are reflected together, more than than considered in isolation. This study valued a bibliographic methodology exploring the works of Paulo Freire (1967, 2003, 2005, 2014, 2019); Mignolo (2003, 2007, 2010, 2017); Ballestrin (2013); Maldonado-Torres (2007, 2008) and other thinkers of decolonial epistemology.
Keywords: Ideology. Decoloniality. Education. Policy.